(untitled) (World Bulletin of Social Sciences, 2023)
A dynamic portrait appears in the form of separate details scattered throughout the novel, in cases where the work does not have enough space for a detailed description of the character’s appearance. The writer can repeatedly refer to the portrait in order to enrich the character with new aspects, to record changes in his appearance and behavior. In describing the hero, Ulugbek Hamdam limits himself to only a few bright details, and allows the reader to fully imagine him, which, of course, can only be done by a meticulous reader. So, the writer’s goal is to invite the reader to inter-spiritual communication